Tabu, Stigma, dan Kebisuan: Mengurai Kompleksitas Inses dalam Struktur Masyarakat - Misrah, Misrah; Sazali, Hasan (Program Studi Pengembangan Masyarakat Islam, 2023)
This study aims to unravel the complexity of the incest phenomenon within societal structures and explore its impact through a critical lens, focusing on the taboos, stigma, and silence contributing to its persistence. The adopted methodology is content analysis on discussions about incest on the social media platform Twitter, using the Keyhole content analysis application to collect and analyze data. The findings indicate that incest triggers a variety of responses on Twitter, with conversations often limited by stigma and silence. Sentiment analysis reveals varied responses from users, including positive, neutral, and negative attitudes towards incest. The surge in discussion activity about incest reflects a high interest in the topic and the need to discuss it openly, despite facing challenges such as stigma and silence surrounding the issue. This research underscores the importance of education and broader societal awareness to overcome the stigma and silence related to incest, as well as to enhance understanding and more effective prevention.